2017
DOI: 10.1002/hed.24796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of venous outflow tract on survival of osteocutaneous free fibula flaps for mandibular reconstruction: A 14‐year review

Abstract: Venous thrombosis of free fibula flaps is more common than arterial thrombosis. Venous stasis in larger vena comitantes may be a contributing factor to microvascular compromise. Anticoagulation and/or handsewn anastomosis may be beneficial if the veins are larger than 4.0 mm in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Chang et al, analyzing a large series of fibula OSC flaps for mandible reconstruction, found that in all the flaps that underwent emergent re-exploration (due to venous thrombosis) the size of the pedicle vein was significantly larger than the size of recipient vein. 30 Another possible explanation for the high take-back rate might reside in the type of reconstruction accomplished with this flap. Nine fibula flaps (34.6%) were used in patients with osteoradionecrosis or reconstruction plate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al, analyzing a large series of fibula OSC flaps for mandible reconstruction, found that in all the flaps that underwent emergent re-exploration (due to venous thrombosis) the size of the pedicle vein was significantly larger than the size of recipient vein. 30 Another possible explanation for the high take-back rate might reside in the type of reconstruction accomplished with this flap. Nine fibula flaps (34.6%) were used in patients with osteoradionecrosis or reconstruction plate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The fibula osteocutaneous flap is more prone to vascular thrombosis if ischemia is over 5 h (Chang et al, 2010). Moreover, the most common reason for flap failure is vascular compromise (Chang et al, 2016; Fukuiwa et al, 2008; Kaciulyte et al, 2019; Yu et al, 2009) Although venous thrombosis is observed more frequently compared to arterial thrombosis, it is usually associated with a higher salvage rate (Chang, 2017; Kruse et al, 2010). Venous thrombosis occurred primarily because of a mechanical obstruction due to compression; such as kinking, twisting or hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thrombosis occurred primarily because of a mechanical obstruction due to compression; such as kinking, twisting or hematoma. Therefore, swift correction of the mechanical cause led to a higher salvage rate compared artery‐caused failures (Chang, 2017; Yu et al, 2009). Twisting or kinking of the pedicle due to the acute angle between the pedicle and fibula axis were encountered more frequently than a hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations